2021
DOI: 10.1080/22221751.2021.1978822
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 CRF07_BC transmission dynamics in China: two decades of national molecular surveillance

Abstract: By analyzing an unprecedentedly large, longitudinal HIV-1 CRF07_BC sequence dataset collected from China in the past two decades, we sought to build CRF07_BC lengthwise transmission networks, and understand its transmission dynamics. We divided CRF07_BC into two clusters based on phylogenetic analysis and an estimation of the pairwise genetic distance at 0.7%. Of 6,213 sequences, 3,607 (58.1%) linked to ≥1 other sequence. CRF07_BC was divided into two clusters: 07BC_O and 07BC_N. The 07BC_O is the original CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In recent years, more and more CRF07_BC strains have been detected in MSM in China [26][27][28]. A study showed that CRF_07BC-N has a greater risk of transmission than CRF07_BC-O [13]. In our unpublished studies, we elucidated the transmission trend and scale of the CRF07_BC epidemic recombinant strain from IDUs to heterosexuals and then to MSM in China.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years, more and more CRF07_BC strains have been detected in MSM in China [26][27][28]. A study showed that CRF_07BC-N has a greater risk of transmission than CRF07_BC-O [13]. In our unpublished studies, we elucidated the transmission trend and scale of the CRF07_BC epidemic recombinant strain from IDUs to heterosexuals and then to MSM in China.…”
Section: Discussionmentioning
confidence: 95%
“…CRF07_BC subtype presented two distinct clusters in the phylogenetic tree: CRF07_BC-N, the subcluster that mainly spread among men who have sex with men (MSM); CRF07_BC-O, the subcluster that mainly spread in heterosexuals and injecting drug users (IDUs) [13]. A total of seven clusters were identified for the CRF01_AE subtype (clusters 1-7), plus an additional cluster classified as CRF01_AE-others [14].…”
Section: Demographic Characteristics and Subtype Profile Of The Study...mentioning
confidence: 99%
“…CRF07_BC-O was genetically and epidemiologically similar to the original CRF07_BC, circulating in IDUs and heterosexual individuals (HETs). It was also called CRF07_BC-unclustered or CRF07_BC-Others in some studies (9)(10)(11). CRF07_BC-N is the latest cluster derived from CRF07_BC-O and has mostly been reported in men who have sex with men (MSM).…”
Section: Introductionmentioning
confidence: 99%
“…CRF07_BC-N is the latest cluster derived from CRF07_BC-O and has mostly been reported in men who have sex with men (MSM). It has also been called CRF07_BC-Cluster 1 or CRF07_BC-MSM in some studies (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation